Active and Passive Immunization with Myelin Basic Protein as a Method for Early Treatment of Traumatic Spinal Cord Injury; a Meta-Analysis - Yousefifard, Mahmoud; Madani Neishaboori, Arian; Rafiei Alavi, Seyedeh Niloufar; Toloui, Amirmohammad; Gubari, Mohammed I M; Zareie Shab Khaneh, Amirali; Karimi Ghahfarokhi, Maryam; Hosseini, Mostafa (Archives of Academic Emergency Medicine, 2021)
Introduction: Traumatic spinal cord injury (SCI), as a dangerous central nervous system damage, continues to threaten communities by imposing various disabilities and costs. Early adjustment of the immune system response using Myelin Basic Protein (MBP) immunization may prevent the SCI-related secondary damages. As a result, the current study is designed to review and analyse the evidence on active and passive immunization with MBP for treatment of traumatic SCI. Methods: Medline, Embase, Scopus, and Web of Science databases were systematically searched until the end of 2020. Criteria for inclusion in the current study included pre-clinical studies, which performed passive (injection of MBP-activated T cells) or active (administration of MBP or MBP-modified peptides) immunization with MBP after traumatic SCI. Exclusion criteria was defined as lack of a non-treated SCI group, lack of evaluation of locomotion, review studies, and combination therapy. Finally, analyses were conducted using STATA software, and a standardized mean difference (SMD) with a 95% confidence interval (CI) were reported. Results: Data from 17 papers were included in the present study. Finally, analysis of these data showed that passive immunization (SMD=0.87; 95%CI: 0.19-1.55; p=0.012) and active immunization (SMD=2.08, 95%CI: 1.42-2.73; p<0.001) for/with MBP both have good efficacy in improving locomotion following traumatic SCI. However, significant heterogeneity was observed in both of them. The most important sources of heterogeneity in active immunization were differences in SCI models, route of administration, time interval between SCI and transplantation, and type of vaccine used. In passive immunization, however, these sources were the model of SCI and the time interval between SCI and transplantation. Although, there was substantial heterogeneity among studies, subgroup analysis showed that active immunization improved locomotion after traumatic SCI in all tested conditions (with differences in injury model, severity of injury, method of administration, different time interval between SCI to vaccination, etc.). Conclusion: The results of the present study demonstrated that immunization with MBP, especially in its active form, could significantly improve motor function following SCI in rats and mice. Therefore, it could be considered as a potential treatment in acute settings such as emergency departments. However, the safety of this method is still under debate. Therefore, it is recommended for future research to focus on the investigation of safety of MBP immunization in animal studies, before conducting human clinical trials.